1985
DOI: 10.1016/0092-8674(85)90245-4
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing accounts for the four forms of myelin basic protein

Abstract: We have isolated cDNA clones encoding the four different forms of mouse myelin basic protein (MBP) and have analyzed the structure of the MBP gene. The three larger forms of MBP differ from the smallest by the inclusion of either or both of two short amino acid sequences at positions 57 and 124 of the smallest protein. The mouse genome contains a single MBP gene comprised of seven exons. The two amino acid sequences present only in the larger MBPs are encoded by separate exons. Furthermore, all exons in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
170
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(172 citation statements)
references
References 31 publications
1
170
1
Order By: Relevance
“…Notably, several other myelin genes are also alternatively spliced (12,13). Among them, PLP and MBP represent possible targets of QKI-5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, several other myelin genes are also alternatively spliced (12,13). Among them, PLP and MBP represent possible targets of QKI-5.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that several myelin-specific genes are alternatively spliced, including myelin basic protein (MBP), proteolipid protein (PLP), and MAG (11)(12)(13). Some splicing events seem to be abnormal in qk v mice.…”
mentioning
confidence: 99%
“…1B). Their expression is enriched during active early myelination in the human and mouse, and in immature OLGs in culture [5][6][7]. These minor MBP isoforms have been observed in the nucleus of primary OLG cultures and OLGs in the mouse brain [25][26][27] and are also enriched in the radial component of compact myelin [28,29].…”
Section: Introductionmentioning
confidence: 97%
“…One of the major families of proteins of CNS myelin arises from the Golli (Gene of Oligodendrocyte Lineage) complex, which is responsible for the developmentally-regulated production of early developmental Golli proteins, and classic myelin basic proteins (MBPs) [3][4][5]. The classic MBP isoforms arise from transcription start site 3 of Golli and are nominally 14-kDa, 17.22/17.24-kDa, 18.5-kDa, and 21.5-kDa in mammals [6,7], and are essential for the formation of compact CNS myelin by OLGs [8,9]. The 18.5-kDa isoform predominates in adult human myelin and has been the most studied.…”
Section: Introductionmentioning
confidence: 99%
“…MBP exists as several different isoforms that result from alternative splicing of the primary mRNA transcripts (de Ferra et al, 1985;Kamholz et al, 1986Kamholz et al, , 1987Kamholz et al, , 1988Streicher and Stoffel, 1989;Asipu and Blair, 1997;Givogri et al, 2000), and multiple isoforms have been cloned and identified from human and mouse . In fish, several MBP cDNAs were reported (Spivack et al, 1993;BrÖ samle and Halpern, 2002).…”
Section: Introductionmentioning
confidence: 99%